Design, modeling and simulation of CMOS-MEMS resonator for biomedical application - Rabih, A.A.S. (IEEE Computer Society, 2014)
CMOS-MEMS resonators have found a broad usage in mass sensing applications especially in biomedical field. This paper reports theoretical calculations and Finite Element Method (FEM) simulation for a proposed microresonator for detection of acetone in exhaled breath as biomarker for diabetes. The resonator is 760 Î¼m long and 340 Î¼m wide with 1.461ng effective mass, 21.331 kHz natural resonance frequency, and 8.867 mHz/pg mass sensitivity. Deposition of 4 Î¼m sensitive layer gives 781 Î¼Hz/ppm gas concentration sensitivity with minimum concentration detection of 1.28 ppm. The operating voltage of this resonator is below 50 V and the static sensing capacitance is 90.84 fF. Due to the reasonable mass sensitivity of the resonator, it could be used for mass sensing applications. Â© 2014 IEEE.